Increasing Percentage of Methane (Ch4) from Biogas with Purification - Abdullah Saleh (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biogas is the one of renewable energies that is the result of fermentation of methanogenic bacteria of biomass or organic substance . The low methane content in biogas is affected by the amount of impurities in the biogas. A membrane that produced from activated zeolite as an adsorbent is used to absorb or reduce the content of impuritiesin the biogas in order to increase methane in the biogas . Variate of research comprise variety the composition ratio of zeolite and clay as materials for zeolite membranes are 30:70 , 50:50 , 70:30 , and the effect of flow rate on the purification were 100% open valve and 50% open the valve . Parameters to determine the quality of the purification results biogas is methane percentage were analyzed by Gas Chromatography. The percentage of methane in biogas purification before treatment was 64.86 % . The results showed that the highest percentage of methane was 72.22 % that generated by biogas purification for zeolite and clay ratio was 70:30 with 100% open valve as the flow rate.